PlantNetwork's Target 8 project: the survey stages - Natacha Frachon; Matthew Jebb; David Rae (Sibbaldia, 2024)
The aim of PlantNetwork’s Target 8 project is to involve botanic and other collections-led gardens throughout Britain (and eventually Ireland also) to cultivate nationally threatened vascular plant species. In this way, if each garden were to ‘adopt’ 2–3 threatened species then the network of British botanic gardens could collectively cultivate almost all of the 204 threatened species found in Britain, and therefore fulfill the requirements of Target 8 of the Global Strategy for Plant Conservation. However, before such a project could start, baseline information on the number and diversity of threatened plants in British ex situ collections was required. Along with this, species dossiers compiling cultivation and conservation details were considered necessary for the success of the project. Furthermore, practical details of the project such as collection and representation needed to be discussed with curators. This paper describes the background, survey work and practical aspects of the project.